Tax rates and tables 2021/22 - Cave, Rebecca (London, England : Zed Books, 2021)
"Tax Rates and Tables contains all the rates, allowances and reliefs introduced by the March 2021 Budget, to take effect for the 2021/22 tax year. This product is intended to be a one-stop reference source to help those dealing with tax issues on a regular basis to quickly find the set of figures they are looking. It is also used an invaluable reference source for students doing professional qualifications. Notes have been added to all tables for clarification. The rates for the devolved territories (Scotland and Wales) are also included as are summaries of the Self-Employed Income Support (SEIS) and Coronavirus Job Retention Scheme (CVJRS) rates introduced by the Government."--
Essential Tables -- Key Tax Dates -- Personal Taxation -- Expenses and Benefits -- Payroll matters -- Shares and share options -- Pensions and investments -- Business profits -- Taxation of companies -- Capital Gains Tax -- Inheritance Tax, gifts and deceased estates -- Capital Allowances -- Stamp Taxes -- VAT -- Other taxes and duties -- National Insurance Contributions (NIC) -- Tax credits and state benefits -- Statutory payments -- HMRC penalties, interest and powers -- Scottish and Welsh Taxes -- International issues -- Index
Includes index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Taxation -- Great Britain -- Rates and tables; Taxation -- Rates and tables; Taxation,Taxation & duties law; Electronic books